2016
DOI: 10.1038/srep35106
|View full text |Cite
|
Sign up to set email alerts
|

mTOR independent regulation of macroautophagy by Leucine Rich Repeat Kinase 2 via Beclin-1

Abstract: Leucine rich repeat kinase 2 is a complex enzyme with both kinase and GTPase activities, closely linked to the pathogenesis of several human disorders including Parkinson’s disease, Crohn’s disease, leprosy and cancer. LRRK2 has been implicated in numerous cellular processes; however its physiological function remains unclear. Recent reports suggest that LRRK2 can act to regulate the cellular catabolic process of macroautophagy, although the precise mechanism whereby this occurs has not been identified. To inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 61 publications
2
67
0
Order By: Relevance
“…LRRK2 kinase inhibition has also been shown to increase levels of the lipdated autophagosome marker LC3-II and the adaptor protein p62 [58, 59]. Recent findings have shown that this kinase-dependent regulation of LC3 lipidation is mediated through Beclin-1 signaling but independent of mTOR/ULK1 signaling, suggesting non-canonincal regulation of autophagy [60]. …”
Section: A Physiological Role For Lrrk2 At Vesicular Membranesmentioning
confidence: 99%
“…LRRK2 kinase inhibition has also been shown to increase levels of the lipdated autophagosome marker LC3-II and the adaptor protein p62 [58, 59]. Recent findings have shown that this kinase-dependent regulation of LC3 lipidation is mediated through Beclin-1 signaling but independent of mTOR/ULK1 signaling, suggesting non-canonincal regulation of autophagy [60]. …”
Section: A Physiological Role For Lrrk2 At Vesicular Membranesmentioning
confidence: 99%
“…In a recent study, Ho and colleagues used several cell models including iPSC‐derived mesDA neurons from G2019S carriers to demonstrate that the mTOR regulator leucyl‐tRNA synthetase (LRS) is phosphorylated by LRRK2 in a genotype‐dependent way, and that G2019S‐associated hyperphosphorylation was linked to impairment of the autophagic system (Ho et al., ). These data suggest that LRRK2 may affect macroautophagy at several levels, including phosphorylation of LRS and Beclin‐1 (Manzoni et al., ).…”
Section: Pd‐associated Lrrk2 Variants In Ipsc‐based Disease Modelingmentioning
confidence: 98%
“…LRRK2 is pivotally involved in regulating proteostasis by its effect on (at least) two major proteostatic mechanisms: on the one hand, it regulates macroautophagy by affecting the phosphorylation status of the key autophagy protein Beclin‐1 (Manzoni et al., ) and the mammalian target of rapamycin (mTOR) regulator Leucyl‐tRNA synthetase (LRS) (Ho et al., ). On the other hand, LRRK2 is under normal conditions degraded via both proteasomal and lysosomal pathways.…”
Section: The Role Of Lrrk2 In the Pathogenesis Of Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In mice, defects in LAP lead to an autoimmune-like response to dying cells and uncontrolled inflammation 18 . Additionally, LRRK2 , a gene associated with Parkinson’s disease, Crohn’s disease, and leprosy has recently been shown to negatively regulate a non-canonical autophagy pathway, suggesting that dysregulation of this pathway may directly influence disease susceptibility 23 .…”
Section: Regulation Of Autophagymentioning
confidence: 99%